Langkah Preventif Penanggulangan Tindak Pidana Narkotika Dalam Perspektif Hukum Pidana - Syahranuddin; Nasution, Chairuni (ARBITRASE: Journal of Economics and Accounting, 2022)
Drug abuse in Indonesia has reached an alarming level, facts on the ground show that 50% of prison residents (rehabilitation hospitals) are drug or substance abusers. The purpose of this paper is to find out how law enforcement against crimes that have been committed by the authorities and has accepted the verdicts of several judges in court as a defense. Drug abuse in Indonesia has reached an alarming level, facts on the ground show that 50% of prison residents (rehabilitation hospitals) are drug or substance abusers. The purpose of this paper is to find out how law enforcement against crimes that have been committed by the authorities and has accepted the verdicts of several judges in court as a defense. Hopefully, this paper can be used to prevent the spread of drug abuse or circulation, but in fact more law enforcement is causing an increase in drug trafficking